Strategi Transformasi Bisnis atas Layanan Sistem Informasi di dalam kelompok usaha PT. Krakatau Steel - , Chandra Baskoro Budi Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the position of joint information system services (Clouds) conditions associated with the needs of businesses within the group of PT Krakatau Steel, the service industry from competition with the information systems (Clouds), as well as to analyze the Key Success Factor PT Krakatau IT as a manager and service providers shared information systems (Clouds) to face the competition and also to analyze the strengths and weaknesses, and threats and opportunities for PT Krakatau IT services, especially in the management of shared information systems (Clouds). In addition, also to evaluate the business strategy that is used PT. Krakatau IT, whether it is still effectively applied in the face of competition. Data for the position of joint information system services (Clouds) conditions associated with the needs of businesses within the group of PT Krakatau Steel is used in this study is the result of the workshop data - Cloud Discovery workshop in July of 2011. Then the data obtained were analyzed using analysis of industry competition (five forces), key success factors and SWOT analysis. The results obtained in this study found that the business prospects of shared information systems services (Clouds) conditions associated with the needs of business people in the group of PT Krakatau Steel of industrial competition with the information system services (Clouds) has considerable potential and relatively low levels competition occurs. In addition, the obtained key success factor for the company, internal and external forces, and are still effective competitive strategy implemented by PT Krakatau IT.